Analysis of Artificial Intelligence Training Indicators According to the Results of Russian Universities Monitoring - T. V. Ryabko; V. A. Gurtov; I. S. Stepus (Высшее образование в России)
Artificial intelligence (hereinafter referred to as AI) is currently an area of strategic importance and a key technology ensuring a new digital economy development in Russia. Qualified AI specialist's training plays an important role in achieving ambitious AI-related goals as stated in government documents. The article presents survey results of more than 200 Russian universities, which enabled to create indicators characterizing both current and planned training volumes of AI specialists.According to the research results, Russian universities have responded quickly to the AI market development. Since 2019, they have been enrolling students at AI learning programs by intensifying training volumes annually. More than half of all AI learning programs are implemented within the «09.00.00 Informatics and Computer Science» and «01.00.00 Mathematics and Mechanics» majors/ specialties. AI specialist training in Russian universities is largely carried out at the expense of budgetary funds. The number of students enrolled at the AI learning programs is much higher for the bachelor programs.The specialists’ graduation in AI-related education programs was evaluated until the year 2025. The authors have also analyzed the best foreign practice in AI specialists training and proposed some measures to increase training volumes of AI specialists at Russian universities, for example, re-orienting higher education programs in the IT field at AI-related technologies. It is important that AI learning programs take into account recruitment needs projection in terms of training volumes and skills profiles.